2006
DOI: 10.1203/01.pdr.0000238247.86041.19
|View full text |Cite
|
Sign up to set email alerts
|

Status of Cellular Rather Than Humoral Immunity is Correlated with Clinical Outcome of Enterovirus 71

Abstract: ABSTRACT:We valuated specific cellular and humoral immune response of cases of enterovirus 71 (EV71) infection and correlated immune response with clinical outcome. After obtaining informed consent, we enrolled 30 EV71 cases including 7 cases with brainstem encephalitis plus pulmonary edema, 12 cases of CNS (CNS) involvement and 11 uncomplicated cases. We measured antibodies specific to EV71, lymphocyte proliferation response and EV71-stimulated cellular response of Th1/Th2 cytokines and chemokines. The 7 EV71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 29 publications
7
92
2
Order By: Relevance
“…To date, the only commercially available XO inhibitor is allopurinol, a purine analogue in clinical use for more than 30 years. Flavonoids [1], and certain other phenols [2], and tannins as well as coumarins [3], plant growth regulators [4] and phenolic compounds [5] have all been reported to be potent XO inhibitors. The putative therapeutic effects of many traditional medicines have been ascribed to flavonoids in particular due to their enzyme inhibitory and antioxidant activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the only commercially available XO inhibitor is allopurinol, a purine analogue in clinical use for more than 30 years. Flavonoids [1], and certain other phenols [2], and tannins as well as coumarins [3], plant growth regulators [4] and phenolic compounds [5] have all been reported to be potent XO inhibitors. The putative therapeutic effects of many traditional medicines have been ascribed to flavonoids in particular due to their enzyme inhibitory and antioxidant activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…9 EV71 was shown to be responsible in China for most of the fatalities associated with severe neurological manifestations ranging from aseptic meningitis to acute flaccid paralysis and brainstem encephalitis in children < 5 years of age. 6,10 Chang et al 11 reported that an extensive analysis of clinical observations showed that humoral immunity did not differ significantly among cases of different clinical severity, and most of the severe EV71 cases had a lower cellular T helper type 1 cytokine level plus a weaker lymphocyte proliferation response. The cellular and humoral immune responses, such as represented by T cells and the interleukin-6 (IL-6) driven response, are both essential for decreasing the viral load and mortality in EV71-infected mice.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Blood samples were obtained on days 1-7 after onset, discharge from the hospital (day [7][8][9][10][11][12][13][14] and the fully recovered stage (defined as 1 month after illness onset), respectively. All samples were collected specifically for this study and were coded to protect confidentiality.…”
Section: Recruitment and Sample Collectionmentioning
confidence: 99%
“…There is an increasing body of research which indicates that cellular and not humoral immunity determines the clinical outcome of EV-A71 infections. In the most severe cases with pulmonary edema, blood samples showed lower levels of cellular cytokines and interferons (TNF-α, IL-1β and IL-6), while there was no difference in the level of neutralizing antibody (NtAb) titers between mild, severe and fatal cases (8). Many diseases such as measles, mumps, influenza, rotavirus and rubella have safe and effective LAVs, testifying to the success and potential of LAVs.…”
Section: Introductionmentioning
confidence: 99%